Applying citizens' juries to the Global South: Final report - Vollan, Björn; Burger, Max; Nilgen, Marco (CGIAR System Organization, 2024)
This report presents the preparation, implementation, outcomes, and policy implications of a total of four citizens’ juries conducted in Bogotá, Colombia, as part of the One-CGIAR Mitigate+ initiative. These juries serve as a model for participatory governance, providing an inclusive forum for citizens to deliberate on complex socio-environmental challenges. In our case, deforestation in the Amazon and its relation to the sustainability of food systems in Colombia. By engaging diverse voices and fostering informed dialogue, the juries offer innovative solutions that balance local priorities with global environmental goals.